1938
DOI: 10.1084/jem.68.6.923
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Cytopenia (Vitamin M Deficiency) in the Monkey

Abstract: Young rhesus monkeys (Macaca mulatta) were given a diet containing casein, polished rice, whole wheat, salt mixture, sodium chloride, cod liver oil, and ascorbic acid. They developed a syndrome characterized by anemia, leukopenia, and loss of weight. Ulceration of the gums and diarrhea were common, and death occurred between the 26th and 100th day. 4 monkeys were given the deficient diet supplemented with 1 mg. of riboflavin daily, and these developed the characteristic signs and died. in periods of time simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1939
1939
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Ulcerative lesions of the gums have been described recently in monkeys on B2 complex deficiencies (9a) (9c) (16) (20). However, to our knowledge, the extension of these lesiorns to the buccal or labial mucosa has not been recorded.…”
Section: Discussion Of Tablementioning
confidence: 84%
See 1 more Smart Citation
“…Ulcerative lesions of the gums have been described recently in monkeys on B2 complex deficiencies (9a) (9c) (16) (20). However, to our knowledge, the extension of these lesiorns to the buccal or labial mucosa has not been recorded.…”
Section: Discussion Of Tablementioning
confidence: 84%
“…The diagnosis of scurvy was confirmed at autopsy by the findings of hemorrhage into the joints, subperiosteum, and in one instance, into the gastrointestinal tract. (16) (20), leucopenia (9c) (20), and diarrhea (9a) (20) have been observed in monkeys; and diarrhea has been described in other species (17).…”
Section: Discussion Of Tablementioning
confidence: 99%
“…No detailed account of the physiological work, which is treated thoroughly in the review of Berry and Spies (5), can be given here. It will be sufficient to say that two well-studied dietary factors for animals, i.e., "vitamin M," without which monkeys develop a fatal blood disorder characterized by leucopenia and sometimes anemia (53), and "vitamin B,," lack of which results in poor growth and macrocytic hyperchromic anemia in chicks (28), and several growth factors for the bacteria Lactobacillus casei and Streptococcus lactis R (for a complete bibliography see reference 5) variously known as "norite eluate factor," "folic acid," "L. casei factor," "SLR factor," etc., are considered to be, if not identical, very closely related, and the name "folic acid" appears now to be applied indiscriminately to various members of the group. Crystalline substances corresponding to four of the above have been isolated, i.e., vitamin B, from both liver and yeast (6,63), vitamin B, conjugate from yeast (64), and two L. casei factors, one from fermentation products and one from liver (35,90).…”
Section: A Dietary Factors Related To Folic Acid and Their Interrelamentioning
confidence: 99%
“…This unknown substance was later named ‘Wills’ factor’ by Janet Watson and William Castle (1897–1990) [4] when they confirmed that the ‘new hemopoietic’ principle or Wills’ factor was found in a different fraction of liver extract from that which was curative for pernicious anemia. Additional factors were described during the same period which were active against nutritional pancytopenia in monkeys [5,6] or required as growth [7,8] or anti-anemia factors [9,10] in chicks. Because these substances were impure and their identity with Wills’ factor could neither be deduced nor tested, they received a variety of individual designations ranging from vitamin M (monkey) [6] to vitamin B c (chick) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additional factors were described during the same period which were active against nutritional pancytopenia in monkeys [5,6] or required as growth [7,8] or anti-anemia factors [9,10] in chicks. Because these substances were impure and their identity with Wills’ factor could neither be deduced nor tested, they received a variety of individual designations ranging from vitamin M (monkey) [6] to vitamin B c (chick) [10]. The report of vitamin B c by Albert Hogan (1884–1961) and Ernest Parrott (1903–1994) [10] also provided investigators with a useful tool – the chick anemia assay – for evaluating unidentified hematopoietic substances.…”
Section: Introductionmentioning
confidence: 99%